2022
DOI: 10.1155/2022/8279357
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical Manifestations, Imaging Features, and Pathogenic/Prognostic Risk Factors for Temporomandibular Disorders (TMD): A Case-Control Study Based on Psychogenic Factors of Patients

Abstract: Objective. To survey the clinical manifestations and imaging features of temporomandibular disorders (TMD) and analyze the risk factors for pathogenesis/prognosis through a case-control study based on psychogenic factors of patients. Methods. According to the inclusion criteria, 200 adult patients were randomly enrolled from the maxillofacial department of our hospital from January 2020 to May 2021, including 100 patients with TMD as the study group and 100 healthy patients as the control group. The study grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…When further imaging is desired, CBCT and MRI are the diagnostic imaging techniques most commonly used in the field of dentistry to aid the diagnosis of TMD [ 29 ]. While CBCT is optimal for viewing skeletal and dental tissues which are especially useful in identifying degenerative joint diseases such as osteoarthritis [ 30 ], MRI is considered to be the gold standard when assessing the articular disc in terms of location and morphology [ 29 , 31 ] as MRI can provide early detection of disc abnormalities and the presence of joint effusion [ 32 ]. All disc-related TMD problems can be confirmed by MRI when indicated [ 31 ].…”
Section: Diagnostic Approachesmentioning
confidence: 99%
“…When further imaging is desired, CBCT and MRI are the diagnostic imaging techniques most commonly used in the field of dentistry to aid the diagnosis of TMD [ 29 ]. While CBCT is optimal for viewing skeletal and dental tissues which are especially useful in identifying degenerative joint diseases such as osteoarthritis [ 30 ], MRI is considered to be the gold standard when assessing the articular disc in terms of location and morphology [ 29 , 31 ] as MRI can provide early detection of disc abnormalities and the presence of joint effusion [ 32 ]. All disc-related TMD problems can be confirmed by MRI when indicated [ 31 ].…”
Section: Diagnostic Approachesmentioning
confidence: 99%
“…Psychological methods include the following: modifying ways of thinking about pain (misconceptions about pain) that cause prolonged suffering and disability replacing a sense of helplessness with a sense of control over pain and one's own life developing strategies for adequate and effective pain management returning to work and promoting an active lifestyle [ 126 , 127 ] …”
Section: The Essence Of the Mattermentioning
confidence: 99%
“…(i) modifying ways of thinking about pain (misconceptions about pain) that cause prolonged suffering and disability (ii) replacing a sense of helplessness with a sense of control over pain and one's own life (iii) developing strategies for adequate and efective pain management (iv) returning to work and promoting an active lifestyle [126,127] It must be remembered that efective pain control requires a multidimensional approach, aiming to reduce the pain but also to improve the patient's quality of life.…”
Section: 22mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%